The Effects of the Prosperity Gospel on Non- Pentecostal Churches in Mansa District, Zambia - Mulonga, Mellanie; Hachintu, Joseph K. (International Journal of Humanities, Social Sciences and Education, 2023)
The focus of this article was to explore the effects of the prosperity gospel on non-Pentecostal Churches in Mansa Township of the Luapula Province in Zambia. The study was significant in the sense that it contributed towards the contemporary discussion on the prosperity gospel and how it has affected non-Pentecostal churches not only in Luapula Province but the nation as a whole. Besides, it was hoped that the finding of the study would add to the body of knowledge and literature on the effects of the prosperity gospel in general. Theoretically underpinned by Marx Weber's (1930) essay on “The Protestant Ethic and the Spirit of Capitalism” with special focus on Calvin's doctrine, the study drew upon the data obtained through qualitative research strategy from 25 respondents. One-on-one interviews and Focus Group Discussions were conducted on clergymen, the youth, laymen and women from Neo-Pentecostal churches and Non-Pentecostal churches while data were analysed thematically. The findings of the study were that the prosperity gospel had effects both negative and positive on non-Pentecostal churches. Negatively, the gospel had made the non-Pentecostal churches compromise in the mode of worship, led to membership stealing, and made people become lazy and have dual membership. Positively, it contributed to the evolution of the Charismatic Renewal Groups. Finally, it was discovered that the prosperity gospel had much influence on the women and the youths causing them to move from their mainline churches into Pentecostalism, exacerbating the rise of Pentecostalism in Mansa Township.
free